Membranotropic action of lauric acid, fenspiride and kaoline in model lipid membranes: role of lipid composition - Vashchenko, O. V.; Budianska, L. V.; Kasian, N. A.; Lisetski, L. N. (Biophysical Bulletin, 2018)
Background: Model lipid membranes are widely used nowadays to elucidate membranotropic action (MA) of pharmaceuticals as well as for development of liposomal drugs. Meanwhile, membrane lipid composition could substantially affect a drug-membrane interaction.Objectives: Comparision of MA of certain pharmaceuticals on model membranes with various lipid compositions.Materials and methods: By means of differential scanning calorimetry (DSC) lauric acid, fenspiride and kaolin were studied with respect of their effects on phase transitions of model membranes based on hydrated phospholipids. Along with “standard” membrane based on L-α-dipalmitoylphosphatidylcholine (DPPC), a membrane containing cerebrosides (DPPC-C) was used, as well as one composed of DPPC, L-α-dipalmitoylphosphatidylethanolamine and cholesterol (DPPC-DPPE-Chol). According to literature, DPPC and DPPC-C membranes are characterized by lipid phase homogeneity, as distinct from membrane DPPC-DPPE-Chol, where two different lipid phases coexist both below and above phase transition region.Results: It was shown that fenspiride manifested similar MA on membranes of all three types. MA of lauric acid in DPPC and DPPC-C membranes were qualitatively similar, whereas, in DPPC-DPPE-Chol membrane, different effects were observed. As to kaolin, distinctions in its MA were observed even between DPPC and DPPC-C membranes, namely, elevation of phase transition temperatures in DPPC-C membrane and a tendency to their reduction in DPPC one. In DPPC-DPPE-Chol membrane, kaolin markedly lowered phase transition temperatures coupled with opposite changes in cooperativity.Conclusions: By the examples of separated substances it was shown that strong disordering MA may be practically independent on lipid composition of membrane. Lipid rearrangement and cooperativity changes in membrane can be induced not only by incorporation of guest substances in the bulk, but also by their adsorption on membrane surface.The obtained results could be useful in adjustment of model membrane composition for MA studies of different pharmaceuticals.